EARLY FLOWERING 3 interactions with PHYTOCHROME B and PHOTOPERIOD1 are critical for the photoperiodic regulation of wheat heading time. - Maria Alejandra Alvarez; Chengxia Li; Huiqiong Lin; Anna Joe; Mariana Padilla; Daniel P Woods; Jorge Dubcovsky (PLoS Genetics, 2023)
The photoperiodic response is critical for plants to adjust their reproductive phase to the most favorable season. Wheat heads earlier under long days (LD) than under short days (SD) and this difference is mainly regulated by the PHOTOPERIOD1 (PPD1) gene. Tetraploid wheat plants carrying the Ppd-A1a allele with a large deletion in the promoter head earlier under SD than plants carrying the wildtype Ppd-A1b allele with an intact promoter. Phytochromes PHYB and PHYC are necessary for the light activation of PPD1, and mutations in either of these genes result in the downregulation of PPD1 and very late heading time. We show here that both effects are reverted when the phyB mutant is combined with loss-of-function mutations in EARLY FLOWERING 3 (ELF3), a component of the Evening Complex (EC) in the circadian clock. We also show that the wheat ELF3 protein interacts with PHYB and PHYC, is rapidly modified by light, and binds to the PPD1 promoter in planta (likely as part of the EC). Deletion of the ELF3 binding region in the Ppd-A1a promoter results in PPD1 upregulation at dawn, similar to PPD1 alleles with intact promoters in the elf3 mutant background. The upregulation of PPD1 is correlated with the upregulation of the florigen gene FLOWERING LOCUS T1 (FT1) and early heading time. Loss-of-function mutations in PPD1 result in the downregulation of FT1 and delayed heading, even when combined with the elf3 mutation. Taken together, these results indicate that ELF3 operates downstream of PHYB as a direct transcriptional repressor of PPD1, and that this repression is relaxed both by light and by the deletion of the ELF3 binding region in the Ppd-A1a promoter. In summary, the regulation of the light mediated activation of PPD1 by ELF3 is critical for the photoperiodic regulation of wheat heading time.